A Comparative Study of Double Pass Laser Heat Treatment in Medium Carbon Steels - Castro-Cerda, F (SPRINGER, 2025)
Laser heat treatments are carried out in two medium carbon, low-alloyed steels. Each chemistry was tested in two initial conditions: ferrite and pearlite and tempered martensite. The hardened layers were characterized by Vickers hardness measurements and in-depth microstructural analysis. Dictra calculations were carried out to simulate the kinetics of austenite formation and cementite dissolution in both steels. The results show that maximum hardness relates primarily to carbon content, but differences in hardened layer depth and transition zone characteristics were significant. Kinetic calculations showed slower cementite dissolution in chromium-alloyed steels compared to manganese-alloyed ones, while austenite formation was slightly slower in manganese alloys. The hardened layer s microstructure was more homogeneous with an initial microstructure consisting of tempered martensite. Hardness dispersion was greater in ferrite and pearlite initial microstructure. Overall, the study confirmed that austenite nucleation occurs just above A1 during laser heating.